(untitled) (Medico Legal Update, 2020)
Introduction: Stature is one of the most important parameters in the identification of an individual, living or dead. In intact bodies, stature estimation does not pose any problem but when dismembered human body parts are involved, it is of a challenge for the forensic pathologist as these parameters are highly sex, race and age dependent. Materials & Method: The study was conducted in Shridev Suman Subharti Medical College, Dehradun among a total of 158 healthy subjects (17-25 years), comprising 79 males and 79 females. Those with cranio-facial defects were excluded from the study. Mean stature and nasal height were obtained by direct measurement; co-relation co-efficient were obtained and regression equation formulated for estimating stature. Observations & Result: The study showed that in males mean values are significantly higher than females for both stature as well as nasal height; stature (males, 172.3435 ± 6.48442; females, 158.9430 ± 5.64269), nasal height (males, 5.0341±.37075; females, 4.6770±.30431). Nasal height in total subjects and individually in males is significantly (p<0.05) and positively correlated with stature. However, in females it is found to be statistically insignificant. These values can be employed in estimation of stature using the linear regression equation Y = 155.251+ 3.395 (nasal height of Males), Y = 151.170 + 1.662 (nasal height of females). Also, accuracy in predicting sex when mean nasal height is taken as independent variable is more in females as compared to males (F=77.2%,M= 68.4%). Conclusion: Nasal height can be used as a reliable tool in estimating stature, particularly in the males and in females it can be used for determination of sex with accuracy.